Meaning And Function In The English Word: Polysemy And Polyfunctionality (Texas Journal of Philology, Culture and History, 2026)
The following article examines the word as a fundamental unit of language, focusing on the semantic phenomenon of polysemy and its role in shaping meaning and communication. It provides a systematic analysis of polysemy in contrast to homonymy and explores how semantic variation enables lexical economy and contextual flexibility in English. Particular attention is given to the concept of polyfunctionality, which is treated as a grammatical phenomenon dependent on semantic multiplicity and realized through processes such as conversion and adjectivization. Drawing on established linguistic theories and illustrative examples, the article argues that polyfunctionality is possible only on the basis of polysemy, highlighting the interdependence of meaning and grammatical function in the structure of the English lexicon.